Payments for Ecosystem Services What, Where and How? - Quintero, Marcela (2023)
Marcela Quintero CGIAR SEMINAR SERIES Payments for Ecosystem Services: Win-Win Solutions? Co-organized by IFPRI, the CGIAR, and Germany’s Federal Ministry for Economic Cooperation and Development (BMZ) Session at Tropentag 2023 SEP 21, 2023 - 7:45 TO 9:15AM EDT